THE EFFECTIVENESS OF GIVING GINGER HOT DRINKS TO REDUCE NAUSEA AND VOMITING COMPLAINTS IN PREGNANT WOMEN: LITERATURE REVIEW - Faisal Akbar; Rika Ayunniawati; Asma Fida Ulya (UPT Penerbitan Universitas Jember, 2022)
Along with nausea and vomiting, pregnant women enjoy mental, physical, and hormonal changes that lead to many processes, can lead to tissue damage and thus may impair maternal health and fetal development.Initial treatment of pregnancy vomiting may include supplements such as emotional counseling, dietary changes, and administration of ginger wedang. Treatment should be included. The motivation for this literature review is to discover the efficacy of giving ginger wedang to reduce forensic cases of nausea and vomiting in pregnant women. We utilized a literature review that used the keywords 'Ginger (AND) Nausea Vomiting (AND) Pregnancy' and searched for journal articles from 2018 to 2022 using the keyword Schooler. The words